Soil Health and Fertility of Florida-Friendly Edible Landscapes - Tina McIntyre; Rachel Gutner; Tiare Silvasy; Esen Momol (EDIS)
Maintaining an edible landscape using the nine Florida-Friendly Landscaping™ principles provides a practical approach to food production for homeowners and landscaping consultants. Integrating practical pest management strategies, addressing nutrient deficiencies, proper pruning techniques, timely harvesting, and mulching are all practices that contribute to a healthy landscape. This new 8-page publication of the UF/IFAS Environmental Horticulture Department provides homeowners with key Florida-Friendly Landscaping™ concepts and tips to enhance the health and fertility of soils while protecting the environment. Healthy soils result in improved production yields, beautiful landscapes, and a more resilient environment. Written by Tina McIntyre, Rachel Gutner, Tiare Silvasy, and Esen Momol. htps://edis.ifas.ufl.edu/ep624